2006
DOI: 10.1159/000100509
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-Containing Neurons of the Hypothalamic Parvocellular Paraventricular Nucleus of the Jerboa: Plasticity Related to Immobilization Stress

Abstract: The corticotropin-releasing hormone (CRH) neurons of the hypothalamic parvocellular paraventricular nucleus (PVN) have a high potential for phenotypical plasticity, allowing them to rapidly modify their neuroendocrine output, depending upon the type of stressors. Indeed, these neurons coexpress other neuropeptides, such as cholecystokinin (CCK), vasopressin (VP), and neurotensin, subserving an eventual complementary function to CRH in the regulation of the pituitary. Unlike in rats, our previous data showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Using protocols thoroughly validated previously [21,[40][41][42][43], the present work showed that acute immobilization (2 h) or cold exposure (5°C, 4 h) did not affect the EM66 immunoreactivity evaluated by the number of EM66-IR neurons within the pPVN. Consistent with these results, other paradigms such as acute immune stress induced by an ip injection of LPS, known to increase cytokines in brain and plasma [44,45], or central injection of cytokines as IL-1β known to be associated with HPA axis activation, did not affect the number of EM66-IR neurons of the pPVN [21].…”
Section: Discussionsupporting
confidence: 71%
“…Using protocols thoroughly validated previously [21,[40][41][42][43], the present work showed that acute immobilization (2 h) or cold exposure (5°C, 4 h) did not affect the EM66 immunoreactivity evaluated by the number of EM66-IR neurons within the pPVN. Consistent with these results, other paradigms such as acute immune stress induced by an ip injection of LPS, known to increase cytokines in brain and plasma [44,45], or central injection of cytokines as IL-1β known to be associated with HPA axis activation, did not affect the number of EM66-IR neurons of the pPVN [21].…”
Section: Discussionsupporting
confidence: 71%
“…Intragastric administration of nutrients that promote satiety (eg, select amino acids) also triggers OXT gene expression and OXT neuronal activation in mice. Importantly, OXT neurones or terminals co‐express other anorexigens, including corticotrophin‐releasing hormone, nesfatin‐1 and cholecystokinin (CCK), and OXT appears to contribute to and/or potentiate the hypophagic action of nesfatin‐1, CCK and leucine in rats and mice. OXT neuronal activation is modified by feeding regulatory peptides either directly (via synapses formed with OXT cells) or indirectly (as an element of broader circuits).…”
Section: Oxytocin and Short‐term Control Of Food Intake: Key Findingsmentioning
confidence: 99%
“…Among them, we focused on the gene encoding cholecystokinin (Cck) as a target candidate for trial antidepressant drugs and as a modulator of the stress responses in the PVN. CCK is a neuropeptide that is involved in feeding, memory formation, and anxiety behavior, and it is expressed in both CRH-and AVP-containing neurons of the PVN (Barakat et al, 2006;Beinfeld et al, 1980;Mezey et al, 1986;Vanderhaeghen et al, 1980). It has been reported that the administration of stress or glucocorticosteroids upregulates Cck mRNA expression in the PVN (Cournil et al, 2000;Kim et al, 2003).…”
Section: Relevance Of the Genes Downregulated By Ecs In The Pvn To Mood Disordersmentioning
confidence: 99%